The images of "El instante de peligro" (2015) by Miguel Ángel Hernández: fleeting reverberations between past and future - Candeloro, Antonio (Tropelías: Review of Literary Theory and Comparative Literature, 2023)
El instante de peligro is a novel that is presented as a love letter sent to a dead recipient and that talks about art and photography as doors to the past, about the enigma of time and, finally, about writing as the only tool we have to remember the past and glimpse the future. The proposed analysis will focus on the meaning acquired by the images that guide the written text in relation to some emblematic works of contemporary art, from Past remains, by Tatiana Abellán, to Andy Warhol’s avant-garde films, including Les amants de Magritte and Cézanne and the importance of the shadow in his first pictorial works, as well as in the very plot of Hernández’s novel.